The Impact of Resource Bricolage on Entrepreneurial Orientation in Start-ups: The Moderating Roles of TMT Heterogeneity and TMT Behavioral Integration - Xiaobao, Peng; Rui, Guo; Jiewei, Zu; Xiaofan, Song (Frontiers in Psychology, 2022)
Prior studies demonstrate the role of resources in shaping a firm’s entrepreneurial orientation from the resource-based view. We expand this line of research by theorising and testing the impact of resource bricolage on entrepreneurial orientation. Based on the data of 295 start-ups, we find that when start-ups face resource constraints, the strategy of resource bricolage has a significant positive effect on entrepreneurial orientation, and the relationship is positively moderated by top management team (TMT) heterogeneity. Meanwhile, the relationship is negatively moderated by TMT behavioral integration. The results are expected to provide theoretical guidance for start-ups to overcome resource constraints and achieve smooth survival and growth.